ANCIENT RESTORATION PRACTICES IN THE CITY OF PERGE - Adem YURTSEVER (Journal of Ancient History and Archaeology)
This study examines ancient restoration practices in the Pamphylia Region, focusing particularly on the city of Perge. It builds upon T. Ismaelli's extensive studies of Roman Imperial Period architecture and restoration methods, supplementing them with new examples specific to Pamphylia. Various restoration methods were identified and analyzed using archaeological evidence, including metal clamps, new marble inserts, and detailed repair processes aimed at extending the lifespan of architectural elements. The findings highlight the period's advanced engineering and architectural skills, demonstrating how these techniques were applied to preserve and restore significant public and private buildings. Additionally, the research categorizes these restoration practices and details techniques such as replacing damaged sections with new materials and reinforcing weakened structures using innovative methods. This detailed examination enriches the literature on ancient restoration practices in Pamphylia and interprets studies on the restoration of ancient architecture through tabular analysis. The study underscores the importance of these practices in preserving cultural heritage and offers a framework for future research.